Interleukin-10 gene –1082 G/A polymorphism in cervical cancer and cervical intraepithelial neoplasia: Meta-analysis. (December 2014) - Zhang, Shuo; Kong, Ya-Lin; Li, Ya-Li; Yin, Yan-Wei
Objectives: To assess the association between polymorphism in the interleukin (IL)-10 promoter region of 1082 G/A and the risk of cervical cancer and/or cervical intraepithelial neoplasia (CIN), using meta-analysis. Methods: The electronic literature databases PubMed®, Embase®, Web of Science, CBMdisc and CNKI were searched for relevant studies. The strength of association between IL-10 gene −1082 G/A polymorphism and cervical cancer and/or CIN was measured using pooled odds ratios with 95% confidence intervals in four genetic models: allelic model (A allele versus G allele); additive model (A/A versus G/G); recessive model (A/A versus G/A+G/G); dominant model (A/A+G/A versus G/G). Results: Eight studies involving 1983 cases and 1618 controls were identified and included in the meta-analysis. No significant associations were found between IL-10 gene −1082 G/A polymorphism and cervical cancer and/or CIN in any of the genetic models. Conclusions: IL-10 gene −1082 G/A polymorphism does not appear to be associated with the risk of cervical cancer and/or CIN.